Multi-Protection of DL0410 in Ameliorating Cognitive Defects in D-Galactose Induced Aging Mice - Lian, Wenwen; Jia, Hao; Xu, Lvjie; Zhou, Wei; Kang, De; Liu, Ailin; Du, Guanhua (Frontiers in Aging Neuroscience, 2017)
D-galactose has been reported to accelerate senescence in rodents, accompanied by a decline in learning and memory. We used a model of D-galactose-induced amnesia for the efficacy evaluation and pharmacologic studies of active compounds against Alzheimer’s disease. DL0410 is a potent inhibitor against acetylcholinesterase (AChE) and, in the present study, the effect of DL0410 was evaluated in this model. We found that DL0410 could significantly improve the learning and memory of D-galactose induced aging mice in a series of behavioral tests: novel-object recognition test, nest-building test, Morris water maze test, and step-through test. Pharmacologic studies were conducted from several aspects: the cholinergic system, mitochondrial respiration, oxidative stress, neuroinflammation, apoptosis, and synaptic loss. The acetylcholine level and AChE activity were not altered by D-galactose but were slightly affected by DL0410 in the brain. DL0410 could significantly improve decreased mitochondrial respiration in the NADH chain and FADH2 chain, and protect mitochondrial ultrastructure. DL0410 reduced the accumulation of advanced glycation end products (AGE) and malondialdehyde (MDA) and increase the total antioxidant capability of the brain via an increase in activity of catalase, glutathione peroxidase (GPx), and superoxide dismutase (SOD). RAGE expression was inhibited by DL0410, followed by the decreased activation of astrocytes and microglia. Subsequent phosphorylation of NF-κB was also reversed by DL0410, with lower expression of COX2 and iNOS. With respect to apoptosis, the activation of caspase 3 and cleavage of PARP were downregulated significantly by DL0410, after the inhibition of phosphorylation of JNK induced by inflammation and oxidative stress. Synaptic protection by DL0410 was also demonstrated. These data suggest that mitochondrial protection has a primary role in the ameliorating effect of DL0410 on the impaired learning and memory, oxidative stress, inflammation, apoptosis and synaptic loss induced by D-galactose. DL0410 is a promising candidate for the treatment of aging-related Alzheimer’s disease, and this study lays an important foundation for its further research and development.